Risk factors for postpartum hemorrhage in twin pregnancies with cesarean section - Lan, Yehui; Xu, Anjian; Lu, Xinyue; Zhou, Yujia; Wang, Jianping; Hua, Ying; Dong, Ke (Frontiers in Medicine, 2024)
The rates of twin pregnancies and cesarean section have increased in recent years, and both of them are at high risks of postpartum hemorrhage (PPH). However, few studies have concentrated on the risks of PPH in twin pregnancies and cesarean deliveries. In this study, we aimed to identify the risk factors for PPH among twin-pregnant women with cesarean section. This was a retrospective observational study including 1649 women with twin pregnancies delivered by cesarean section from 2016 to 2022 in the Second Affiliated Hospital of Wenzhou Medical University, China. The eligible women were divided into PPH group (n = 116) and non-PPH group (n = 1533) according to the blood loss after delivery within 24 hours. The baseline maternal and perinatal characteristics were compared between the two groups. Logistic regression analysis was conducted to identify the potential risk factors for PPH. We found nulliparity, assisted reproductive technology (ART) usage, preeclampsia or HELLP syndrome, placenta previa, placenta accreta and general anesthesia were more common in PPH group than non-PPH group (P < 0.05). Women in PPH group had higher maternal body mass index at delivery and higher combined birthweight of the twins than non-PPH group, but had lower parity (P < 0.05). Seven independent risk factors for PPH were identified after logistic regression analysis: ART usage (OR 2.354 95%CI 1.357-4.083, P = 0.002), preeclampsia or HELLP syndrom (OR 2.605, 95%CI 1.471-4.616, P = 0.001), placenta previa (OR 7.325, 95%CI 3.651-14.697, P < 0.001), placenta accreta (OR 6.296, 95%CI 1.316-30.12, P = 0.021), thrombocytopenia (OR 1.636, 95%CI 1.056-2.535, P = 0.027), general anesthesia (OR 2.394, 95%CI 1.223-4.686, P = 0.011), and combined birthweight (OR 1.00032, 95% CI 1.00005-1.00059, P = 0.020) . Collectively, in women with twin pregnancies delivered by cesarean section, the use of ART, preeclampsia or HELLP syndrome, placenta previa, placenta accreta, thrombocytopenia, general anesthesia and the combined birthweight were identified as independent risk factors for PPH. More attention should be paid to women with these risk factors.